European asylum policy before and after the migration crisis - Timothy J. Hatton (IZA World of Labor, 2020)
The migration crisis of 2015–2016 threw the European asylum system into disarray. The arrival of more than two million unauthorized migrants stretched the system to its breaking point and created a public opinion backlash. The existing system is one in which migrants risk life and limb to gain (often unauthorized) entry to the EU in order to lodge claims for asylum, more than half of which are rejected. Reforms introduced during the crisis only partially address the system's glaring weaknesses. In particular, they shift the balance only slightly away from a regime of spontaneous asylum-seeking to one of refugee resettlement.
Keywords: J11; J61; 330; migration crisis; refugees; European asylum policy